Studium przypadku jako metoda nauczania etyki biznesu - Szulczewski, Grzegorz (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2012)
The Harvard Business School introduced the practice of teaching business ethics through case study. This article presents the characteristics of teaching business ethics through case study. First we answered the question: how to build a case study? Then we showed how moral problems are solved through a case study. Next we showed the types of case study (teaching goal, kind of moral issues, the role of ethics and problems of this method of teaching). Then we answered the question how to use the methods of philosophy for the analysis of case study. We have considered the problem of the moral level of the students who solved the case study. Turning to practical matters provides instructions for building a case study. Finally, we showed that solving the case study not only provides a valuable method of teaching ethics in the business, but is valuable for professional ethics.